2017
DOI: 10.1016/j.ijscr.2017.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Mucocele complicating stapled hemorrhoidopexy

Abstract: HighlightsMucocele is a variant of rectal pocket.Mucocele is a rare complication after stapled procedure.Mucocele has problems of differential diagnosis with paraectal lesion, especially abscess.It is usually treated with transanal approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…With this protracted cyst development, the amount of mucus within the mucocele increased slowly and, therefore, could be accommodated by the tissues or contained the slight occluded portion of the cystic lesion. It has been reported that the size of a mucocele may vary over time and that mucocele-related symptoms may be intermittent due to the possibility of partial drainage of the mucus inside the rectal lumen 7. In our case, the patient had not noticed any discharge of liquid from his anus.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…With this protracted cyst development, the amount of mucus within the mucocele increased slowly and, therefore, could be accommodated by the tissues or contained the slight occluded portion of the cystic lesion. It has been reported that the size of a mucocele may vary over time and that mucocele-related symptoms may be intermittent due to the possibility of partial drainage of the mucus inside the rectal lumen 7. In our case, the patient had not noticed any discharge of liquid from his anus.…”
Section: Discussionmentioning
confidence: 47%
“…Each of these diseases differs slightly with regard to the site of occurrence and clinical symptoms, with MRI being useful for differential diagnosis9 and transanal ultrasound necessary to confirm the diagnosis of a mucocele 7. The salient findings of a mucocele on imaging include a uniform internal cystic mass, with high T2 signal intensity and absence of internal nodules (mucous lake).…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion of anal and low rectal cancers and polyps is an important aspect of their management. Other differentials include mucocele, inflammatory bowel disease, neurofibroma, GIST, and leiomyoma [ 3 ]. Clinical findings and background of previous fistula treatment in our case led to the decision to perform an MRI scan rather than a flexible sigmoidoscopy initially.…”
Section: Discussionmentioning
confidence: 99%
“…When indicated for symptoms, surgery for RM is the treatment of choice [ 12 ]. The surgical options may include mucocele excision or often more simply, evacuation of the mucocele contents, creation of an opening of the cyst into the rectal lumen (marsupialization) with removal of extraneous staples.…”
Section: Discussionmentioning
confidence: 99%
“…In general, SH increased relative risk of haemorrhoid recurrence compared with traditional open haemorrhoidectomy [ 5 , 6 ]. The stapled approach to the haemorrhoid-bearing mucosa has resulted in a unique collection of procedural complications [ 7 11 ] with postoperative rectal mucocele (RM) a particularly rare example [ 12 ]. The clinical presentation by patients with a RM is typically delayed with some asymptomatic cases diagnosed as an incidental finding.…”
Section: Introductionmentioning
confidence: 99%